Demand analysis of perioperative nursing service needs for patients with cervical spondylosis based on the Kano model: a cross-sectional study - LinLing Hu; Lei Wang; Yan Wang; Jing Huang; Ping Dong; Chunmei Luo (BMC Nursing)
Abstract Background This study uses the Kano model as its theoretical foundation to classify the needs of patients with cervical spondylosis according to their perioperative nursing service needs. It defines, prioritizes, and categorizes these needs to identify the core requirements of perioperative nursing services for patients with cervical spondylosis. The aims of this study are to provide high-quality medical and nursing services during the perioperative period for patients with cervical spondylosis and to offer evidence for improving patient satisfaction. The aim of this study was to explore the needs of perioperative nursing services for patients with cervical spondylosis using the Kano model. Methods Using the Kano model as the theoretical framework, a questionnaire on the perioperative nursing service needs of patients with cervical spondylosis was developed through a literature review, semi structured interviews, and expert consultation methods. A cross-sectional survey was conducted on 200 adult patients who received cervical spine surgery in the orthopedics departments of tertiary Grade A hospitals in China from March 2024 to December 2024 to explore the perioperative nursing service needs of patients with cervical spondylosis. Data on the demographic characteristics’ questionnaire and the Kano model-based questionnaire for the perioperative nursing service needs of patients with cervical spondylosis were collected through convenience sampling. Based on the Kano model, the attributes of each requirement are determined, the satisfaction coefficient is calculated, and a two-dimensional matrix graph between demand and satisfaction is constructed. Results A total of 181 valid questionnaires were collected in this study, with a valid response rate of 90.50%. The findings revealed that 26 fundamental attributes were required to meet the perioperative nursing service needs of patients with cervical spondylosis. The Kano model was used to categorize and prioritize the 26 quality attributes. Kano analysis revealed that 20 attributes were categorized as “one-dimensional attributes”, 3 attributes were categorized as “attractive attributes”, 2 attributes were categorized as “must-be attributes”, and 1 attribute was an “indifferent attribute”. A two-dimensional matrix diagram is shown: 22 attributes were located in Predominance Area I; 1 attribute were located in Improving Area II; 1 attribute was located in Secondary Improving Area III; and 2 attributes was located in Reserving Area IV. Conclusion The Kano model revealed that cervical spondylosis patients had a positive attitude toward the need for perioperative nursing services. The one-dimensional and must-be attributes of the perioperative nursing service needs of patients with cervical spondylosis mainly focus on pain management, wound and drainage tube care, swallowing and respiratory care, rehabilitation and positioning care, dietary and nutritional guidance, and disease- and surgery-related knowledge. The attractive attributes primarily concentrate on enhancing family caregiving capabilities, providing multichannel medical information, and maintaining patients’ personal image. It is suggested that medical institutions and medical staff continue to maintain and improve the supply of must-be attributes and one-dimensional attributes services, develop attractive attribute services according to the actual clinical situation, and objectively analyze and optimize the indifferent attribute services.